2010
DOI: 10.1088/0022-3727/43/48/485201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic coatings deposited with an atmospheric pressure microplasma jet

Abstract: Successful plasma polymerisation of a fluorocarbon compound (c-C 4 F 8 ) using an atmospheric pressure plasma jet is described. The source is operated with argon as working gas at a flow rate of 6 slm and 10 -100 sccm admixtures of c-C 4 F 8 . Deposition is limited to a discharge regime with strong localization and was observed for conductive substrates only (Al and Si). The deposition process is characterized by a high local growth rate (40 nm/s) and produces films which show a Teflon-like chemical structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
2
27
0
1
Order By: Relevance
“…As noticeable, the film turns out to have a quite relevant roughness and not a constant thickness on the whole deposition area, in agreement with the results of previous work …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As noticeable, the film turns out to have a quite relevant roughness and not a constant thickness on the whole deposition area, in agreement with the results of previous work …”
Section: Resultssupporting
confidence: 92%
“…The studies performed with this kind of sources demonstrated the effectiveness of non‐equilibrium APPJs in depositing polymeric films by means of monomer polymerization. For example, Bhatt et al pointed out the possibility to employ a non‐equilibrium Ar APPJ to deposit in open air PEG‐like coatings for cell repellent applications, while Vogelsang et al reported the first successful deposition of hydrophobic C:F thin film on conductive substrates with a RF capillary atmospheric pressure microplasma jet. With regard to AA plasma‐polymerization, Donegan and Dowling investigated the water stability, the chemical/morphological characteristics, and the level of protein adhesion of pPAA coatings deposited onto silicon substrates by using two different plasma jet deposition systems.…”
Section: Introductionmentioning
confidence: 99%
“…[31,32,50,51] Indeed, Vogelsang et al, [31] in their work on the deposition of C:F coatings using a RF capillary microplasma jet, reported of a maximum coating thickness of 7.8 mm after 3 min of deposition; Chen et al, [32] reporting on the deposition of pPAA coatings with an atmospheric pressure glow discharge plasma jet, observed a thickness of around 300 nm after a 10 min deposition time. Bashir et al, [50] in their work on the polymerization of hexamethyldisiloxane using a DBD plasma jet, reported about an average thickness of the deposited coating of 662 AE 33 nm after a treatment time of 3 min.…”
Section: Resultsmentioning
confidence: 99%
“…상압 플라즈마를 표면 코팅에 사용한 몇몇 사례들이 최근 문헌 에 보고되어 있는데, DBD 플라즈마를 사용하여 유리와 실리콘 기질 에 소수성 폴리스타이렌(polystyrene) 막을 안정적으로 증착시킨 사례 [3], 불화탄소의 중합 코팅에 상압 플라즈마 제트를 사용한 사례 [11] 등이다. 형광체와 같은 분말 형상 물질의 소수성 코팅에 진공 플라즈 마의 일종인 글로우 방전을 이용한 연구는 문헌에 일부 보고되어 있 으나 [12], 대기압 플라즈마를 이용한 사례는 잘 알려져 있지 않다 [4,13].…”
Section: 서 론unclassified